Análisis de la evolución de afiliados, pensionados y cotizantes en Colombia: proyecciones hasta 2050 y su impacto fiscal (2025)
This research analyses the evolution of the pension system in Colombia, focusing on members, contributors and pensioners of the RAIS and RPM regimes, with projections up to the year 2050. The main objective is to evaluate the fiscal sustainability of the system and its impact on GDP, considering demographic, economic and structural reform factors. The study is based on ARIMA time series models and Monte Carlo simulations to project the future behaviour of the system. Historical trends of members and pensioners are analysed, identifying challenges such as high labour informality, population ageing and low system coverage. Currently, only 25% of workers contribute regularly, while the proportion of older adults continues to increase, putting pressure on public finances.